2016
DOI: 10.3390/v8080216
|View full text |Cite|
|
Sign up to set email alerts
|

Measles Virus Hemagglutinin Protein Epitopes: The Basis of Antigenic Stability

Abstract: Globally eliminating measles using available vaccines is biologically feasible because the measles virus (MV) hemagglutinin (H) protein is antigenically stable. The H protein is responsible for receptor binding, and is the main target of neutralizing antibodies. The immunodominant epitope, known as the hemagglutinating and noose epitope, is located near the receptor-binding site (RBS). The RBS also contains an immunodominant epitope. Loss of receptor binding correlates with an escape from the neutralization by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 61 publications
2
23
0
Order By: Relevance
“…The risk of emergence of MeV mutants that escape vaccine-induced antibody neutralization is negligible. In fact, neutralizing antibodies that are present in sera of vaccinees or subjects with previous wild-type virus infection recognize immunodominant epitopes located in a region of the hemagglutinin protein that is subject to strong structural constraints, since it interacts with different receptors in human cells, such as SLAM, nectin-4, and CD46 [41].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of emergence of MeV mutants that escape vaccine-induced antibody neutralization is negligible. In fact, neutralizing antibodies that are present in sera of vaccinees or subjects with previous wild-type virus infection recognize immunodominant epitopes located in a region of the hemagglutinin protein that is subject to strong structural constraints, since it interacts with different receptors in human cells, such as SLAM, nectin-4, and CD46 [41].…”
Section: Discussionmentioning
confidence: 99%
“…P397L mutation has been found in the genotype H1 strain that originated in China (4). Tahara et al demonstrated that the Japanese H1 strains that possess this mutation are not neutralized by a specific MAb (25). Although the HNE may be an antigenic epitope (30), the advantage of this mutation has yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…5c and 6). Previous research on antigenic epitopes of MeV H showed that the majority of MeV H monoclonal antibodies with neutralizing capability were targeted to the receptor-binding area (Hashiguchi et al, 2011a;Tahara et al, 2016). Accordingly, it is tempting to anticipate that the three BCE motifs in the 16-mers P48, P60 and P63 have the potential to be used as candidates for PPRV multi-epitope vaccine development.…”
Section: Discussionmentioning
confidence: 99%
“…Peste des petits ruminants (PPR) is a highly infectious disease of domestic and wild small ruminants that is caused by PPR virus (PPRV), a member of the genus Morbillivirus that includes rinderpest virus (RPV), measles virus (MeV), canine distemper virus (CDV), phocine distemper virus (PDV), cetacean morbillivirus (CeMV), and feline morbillivirus (FeMV) (Torsson et al, 2016). Clinical symptoms associated with PPR include pyrexia, congestion of mucosal surfaces, ocular and nasal discharge, erosive stomatitis and diarrhea (Liang et al, 2016;Libeau, 2015).…”
Section: Introductionmentioning
confidence: 99%